Respuesta :

Answer:

x=-2  x=2  x = 1/2   x=3

Step-by-step explanation:

f(x) = 2x^4 − 5x^3 − 5x^2 + 20x − 12

Graph

We see that there is a zero at -2

Using synthetic division

-2      2   -5  -5   20  -12

             -4   18   -26  12

     ------------------------------  

         2   -9  13  -6     0

This gives us ( x+2) ( 2x^3 -9x^2 +13x -6)

We see that there is a zero at 2

Using synthetic division  ( 2x^3 -9x^2 +13x -6)

2       2   -9  13  -6

              4   -10  6

     ------------------------------  

         2   -5  3  0

This gives us ( x+2)   ( x-2) ( 2x^2 -5x+3)

We can factor  ( 2x^2 -5x+3)

( x+2)   ( x-2)  ( 2x -1) ( x-3)

Using the zero product property

( x+2)=0   ( x-2)=0  ( 2x -1)=0 ( x-3)=0

x=-2  x=2  x = 1/2   x=3

Ver imagen wegnerkolmp2741o
ACCESS MORE